De bewaking van de Dodendraad in Limburg en de Antwerpse Kempen. Een blik achter de schermen - Vanbussel, Jef (Limburg. Het Oude Land van Loon, 2024)
Keywords: Besetzung; Elektrozaun; Erster Weltkrieg; Kempenland; Militär

De heldinnen van de Eerste Wereldoorlog - Aert, Marina van (Oudheidkundige Kring Kalmthout vzw, 2022)
Keywords: Besetzung; Elektrozaun; Erster Weltkrieg; Fluchthilfe; Kalmthout; Schmuggel; Widerstand

Kolczasty drut śmierci jako strażnik granicy. Nieznany epizod Wielkiej Wojny 1914–1918 na pograniczu holendersko–belgijskim - Żelichowski, Ryszard (Dzieje Najnowsze, 2016)
Abstract: „The Wire of Death as a Border Guard. An Unknown Episode of the Great War 1914–1918 along the Dutch–Belgian Frontier For four long years the First World War changed the relations between the Kingdom of The Netherlands and the Kingdom of Belgium, with the former remaining neutral in the conflict while the latter became a theatre of particularly bloody hostilities. In the province of North Brabant, which was part of the Kingdom of The Netherlands, at a small distance from border with the Kingdom of Belgium there lies a locality bearing the double name of Baarle–Hertog and Baarle–Nassau – a Dutch–Belgian jigsaw composed of 30 enclaves. The German armies decided not to attack the Belgian enclaves since they could not do so without violating the neutrality of the Dutch. In order to prevent the inflow into The Netherlands of volunteers who could come to the aid of the army defending itself in the Yzer river valley, in January 1915 the German troops embarked upon setting up networks of barbed wire along the entire Belgian border (450 kms long) from the Zwin inlet in Knokke to the suburbs of Aix–la–Chapelle. The unique frontier encircling the Belgian enclaves was composed of electric barbed wire known as the „Wire of Death”, which took the lives of numerous victims and was the source of the tragic plight of all thus separated families. The border in question also divided small towns and villages, sometimes in half. The presented text discusses several such instances. The author concentrated predominantly on the functioning of the lethal frontier and the life of people residing on both its sides. He also described the history of Baarle–Hertog, a little– known fragment of free Belgium within Dutch Branat, and its role in obtaining information about the plans and activity of the German occupant.“
Keywords: Baarle-Hertog; Baarle-Nassau; Elektrozaun; Enklave; Erster Weltkrieg

Een Kalmthouts verhaal van „passeurs“ en weggevoerden in 1915–1916 - Aert, Marina van (Calmthoutania, 2015)
Keywords: Besetzung; Elektrozaun; Erster Weltkrieg; Fluchthilfe; Kalmthout; Schmuggel; Widerstand

Borders (The Netherlands) - Abbenhuis, Maartje (1914-1918-online. International Encyclopedia of the First World War, 2014)
The borders of the Netherlands were an important site of war experience for the Dutch, as well as a contested site of war interaction for the belligerents.
Keywords: Elektrozaun; Erster Weltkrieg; Neutralität

De Doodendraad. De elektrische draadversperring aan de Oost- en Zeeuws-Vlaamse grens tijdens de Eerste Wereldoorlog - Vanneste, Alex (Provincie Oost-Vlaanderen, 2014)
Keywords: Elektrozaun; Erster Weltkrieg; Ostflandern; Seeländisch-Flandern

High Voltage Fence (The Netherlands and Belgium) - Vanneste, Alex (1914-1918-online. International Encyclopedia of the First World War, 2014)
In 1915 the Germans built an electric fence along the Belgian-Dutch border, consisting of three lines of wires which were intended to stop all disturbing border activities that might severely harm the military operations and authority of the occupier.
Keywords: Besetzung; Elektrozaun; Erster Weltkrieg; Militär

Hoogspanning aan de Belgisch-Nederlandse grens. De Eerste Wereldoorlog aan de rijksgrens met Baarle - Janssen, Herman (Heemkundekring Amalia van Solms Baarle-Hertog-Nassau, 2013)
Keywords: Baarle-Hertog; Baarle-Nassau; Elektrozaun; Erster Weltkrieg

Kroniek van een Dorp in Oorlog. Neerpelt 1914–1918. Het dagelijks leven, de spionage en de elektrische draadversperring aan de Belgisch-Nederlandse grens tijdens de Eerste Wereldoorlog - Vanneste, Alex (Universitas, 1998)
Keywords: Elektrozaun; Erster Weltkrieg; Neerpelt